Investigation of the structure and properties of PVD coatings and ALD + PVD hybrid coatings deposited on sialon tool ceramics. (August 2018) - Staszuk, M.; Pakuła, D.; Chladek, G.; Pawlyta, M.; Pancielejko, M.; Czaja, P.
Abstract: It was shown in the paper that the operational properties of sialon tool ceramics coated PVD coatings, both in conventional process as well as in hybrid ALD/PVD process, depend mainly on their adhesion to the substrate. The paper presents researches of coating structure made using scanning and transmission electron microscopy. Phase composition analysis was carried out using XRD methods as well as electron diffraction in TEM. Analysis of the chemical composition in coatings micro-areas was made using the EDS method. The microhardness and adhesion of coatings to the substrate were also investigated. Researches shown that the coating of (Ti, Al)N deposited in a hybrid process, i.e. with the prior formation of the ZnO layer by the ALD technique on a ceramic substrate, to ensure the possibility of substrate polarization during the PVD process, makes it possible to obtain coating with significantly better adhesion and better exploitative properties in comparison with a coating (Ti, Al)N obtained by the conventional method. In addition, it was found that the high adhesion and very good exploitative properties of coating (Al, Ti)N are undoubtedly connected with the existence of intermediate zones between the substrate and the coating. Highlights: Adhesion of coatings to substrate is the most important property determining the durability of the coated cutting tools. The coatings obtained by hybrid ALD/PVD processon on sialon ceramics in ensures a much better adhesion than conventionally. High adhesion of (Al, Ti)N coatings to ceramic substrate is conditioned by the existence of transition zones at the interface.